Emosi dan Suasana Hati – Sebuah Pilihan Etis: Haruskah Manajer Menggunakan Kecerdasan Emosional? (Studi Kualitatif terhadap Pengalaman Mahasiswa dalam Organisasi Kampus) - Mario Maulana Wardana; Muhammad Alfin Alfarizi; Muhammad Shoffan Anbiya; Raka Keanu Athala; Sofa Parihah Nurasiah (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study examines how a university student who actively participates in campus organizations perceives and ethically evaluates the use of emotional intelligence (EI) by organizational leaders. Drawing on the ethical dilemma proposed by Robbins, “Should Managers Use Emotional Intelligence?”, this research adopts a qualitative single-case study approach involving an informant whose Myers-Briggs Type Indicator (MBTI) personality type was already known prior to the interview. Data were collected through an in-depth, semi-structured interview with a student actively involved in several campus organizations and committees. The findings reveal that the informant distinguishes ethical from manipulative use of EI primarily through the consistency of a leader’s caring behavior, rather than the leader’s stated intentions. The informant also described an ambiguous experience in which a generally empathetic leader made a unilateral, pressuring decision under time constraints, indicating that EI-driven leadership is not free from ethical tension. The informant’s ENFJ personality type appeared to shape an initial tendency toward trust, later balanced by a more action-based evaluation of leaders’ sincerity. This study contributes a grounded, personality-aware perspective to the ongoing ethical debate on EI in leadership.